Gambaran Kualitas Hidup Pasien Fraktur Femur Pasca Operasi - Ilham Devirxa Jusaf; Ridwan Balatif (Faculty of Medicine, Universitas Andalas, 2021)
Objective: To describe the quality of life in postoperative femoral fracture patients. Methods: This study is a descriptive study with a cross-sectional method. The sample in this study were patients diagnosed with femoral fractures and had surgery at Haji Adam Malik General Hospital Medan from the period July 2015 to December 2018. Data on patient characteristics were taken from medical records while data regarding the quality of life of patients were taken directly by researchers by interviewing patients by telephone. Quality of life was measured using the short form -36 (SF-36). Results: Most of the patients were male (81.5%), with an age range of 25-34 years being the largest age (29.6%) of femoral fracture cases in this study. The most common cause of femoral fractures was traffic accidents (85.2%). The most locations of femur fractures were in the subtrochanteric area and were not specific (25.9%). The most common type of fracture was closed fracture (66.7%). From the results of the assessment of the quality of life subvariable, almost all variables have good scores except vitality. Conclusion: Overall the patient's quality of life variable, about 59.3% of postoperative femoral fracture patients had a good quality of life.